Penerapan Technology Acceptance Model Terhadap Perilaku Pengguna Uang Elektronik - Muthia Harnida; Siti - Mardah (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
The acceptance of new technology generally uses Technology Acceptance Model as an approach model to explain how the users accept new technology. The constructs of the technology acceptance model are perceived ease of use, perceived usefulness, attitude toward using, and actual usage. This research aims to examine whether perceived ease of use and perceived usefulness affect attitude toward using and actual usage of the use of electronic money to obtain empirical evidence on how public acceptance of the use of electronic money, especially among users at private colleges and universities in Banjarmasin. 150 participants participated through questionnaires that were delivered by Google Form. Partial Least Square (PLS) with Smart PLS 3.0 is the tool for analyzing data. The results show that perceived ease of use and perceived usefulness affect attitude toward using and actual usage, and attitude toward using also affects actual usage of the use of electronic money.